2007
DOI: 10.1186/1746-1340-15-1
|View full text |Cite
|
Sign up to set email alerts
|

Postural development in school children: a cross-sectional study

Abstract: BackgroundLittle information on quantitative sagittal plane postural alignment and evolution in children exists. The objectives of this study are to document the evolution of upright, static, sagittal posture in children and to identify possible critical phases of postural evolution (maturation).MethodsA total of 1084 children (aged 4–12 years) received a sagittal postural evaluation with the Biotonix postural analysis system. Data were retrieved from the Biotonix internet database. Children were stratified an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 32 publications
5
47
0
7
Order By: Relevance
“…However, the authors did not specify the angles of thoracic kyphosis and lumbar lordosis, so direct comparison of the angles is impossible. Lafond et al in their study of posture in the sagittal plane in a large population of children and adolescents aged 4-12 observed a significant main effect of age and gender [9]. Cil et al revealed a significant difference among different age groups for thoracic kyphosis and lumbar lordosis angles.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…However, the authors did not specify the angles of thoracic kyphosis and lumbar lordosis, so direct comparison of the angles is impossible. Lafond et al in their study of posture in the sagittal plane in a large population of children and adolescents aged 4-12 observed a significant main effect of age and gender [9]. Cil et al revealed a significant difference among different age groups for thoracic kyphosis and lumbar lordosis angles.…”
Section: Discussionmentioning
confidence: 96%
“…There were 331 girls and 286 boys ages [8][9][10][11][12][13][14][15][16]. All the examined students and their parents/guardians were informed of the procedures and voluntarily signed consent prior to measurements.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the adult standard for body alignment would mischaracterize the greater mobility, flexibility, and the temporary deviations in alignment that occur in children during development 1 as abnormalities. According to Lafond et al, 9 upright posture measurements of children and adolescents might be a useful clinical tool to identify musculoskeletal conditions at early stages during the developmental process and aid prevention.…”
mentioning
confidence: 99%